Ectoparasitos em preás (Galea spixii Wagler, 1831) cativos no Semiárido do Rio Grande do Norte, Brasil - Pereira, Josivania Soares (Universidade Federal Rural do Semi-Árido, 2011)
The wild rodents when bred in captivity may be affected by some infectious or parasitic diseases, which affects the health and welfare of these animals. Based on this, we aimed to work in order to identify the natural ectofauna cavy Galea spixii raised in conditions of captivity in the semi arid region of Rio Grande do Norte and study the behavior of the dynamics of the ectoparasitism more prevalent. The study was performed in 40 specimens adult male of G. spixii captives of Centro de Multiplicação de Animais Silvestres of the Universidade Federal Rural do Semi-Arid. The specimens were anesthetized and examined for ectoparasites during the research, in the months from March to October 2010. All guinea pigs studied were positive for ectoparasites, among them, Amblyomma sp. Demodex sp. and Gliricola quadrisetosa. The latter species was the most prevalent. By linking G. quadrisetosa with the dorsal and lateral body surface area of G. spixii, just in one of the correlations made, showed statistically significant differences (p <0.05), where we noted that the average number of lice recovered from different body regions was greater for female specimens. The climatic period did not influence the frequency of G. quadrisetosa recovered from animals (p> 0.05). From the ectofauna identified in the G. spixii we notify the Demodex sp. as first recorded in this rodent in semi arid conditions in Brazil. The data suggests that body area and the climate did not interfere in infra population of G. quadrisetosa found in G. spixii.
Ectoparasites in guinea pigs (Galea spixii Wagler, 1831) captive in semiarid region of Rio Grande do Norte, Brazil
Keywords: Amblyomma; Demodex; Gliricola quadrisetosa; Rodent; Amblyomma; Demodex; Gliricola quadrisetosa; Rodentia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA